2019
DOI: 10.1177/1053815119873087
|View full text |Cite
|
Sign up to set email alerts
|

Are We Maximizing the Role of Caregivers’ Support Networks in Early Intervention?

Abstract: Part C Early Intervention is intended to build capacity among caregivers of infants and toddlers with special needs to use tailored strategies in natural environments. Satisfaction and perceived strategy use, however, remain unclear. In a Northeastern home-based program, caregivers ( n = 195; 33% response) and providers ( n = 66; 33% response) answered questions on strategy use, whether others are asked to use strategies, and perceived compliance. A subset of providers participated in a focus group. Most provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…These results are partially in line with those found by Edwards [ 21 ] in a USA survey, in which over 80% of the families identified informal caregivers (parents and friends) as the main support network, followed by intermediate supports (groups of parents), and last, formal support networks of professionals. The study of Más, Giné, and McWilliam [ 13 ], with Spanish families attending services with a family-centered approach, also identified the extended family as the main source of emotional support, especially the grandparents of the child.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are partially in line with those found by Edwards [ 21 ] in a USA survey, in which over 80% of the families identified informal caregivers (parents and friends) as the main support network, followed by intermediate supports (groups of parents), and last, formal support networks of professionals. The study of Más, Giné, and McWilliam [ 13 ], with Spanish families attending services with a family-centered approach, also identified the extended family as the main source of emotional support, especially the grandparents of the child.…”
Section: Discussionsupporting
confidence: 90%
“…[ 7 , 15 ]. In a study conducted in the USA by Edwards [ 21 ], over 80% of the participating families identified, as their main supports, informal caregivers, such as grandparents and friends, followed by intermediate supports, such as groups of parents of other children, and last, formal supports provided by professionals. Moreover, in the study conducted by Más, Giné, and McWilliam [ 13 ], Spanish families identified the extended family, particularly grandparents, as the main source of emotional support.…”
Section: Support Network and Family Empowerment In Early Interventionmentioning
confidence: 99%
“…Needs assessments may enhance family, school, and community partnerships by considering the make‐up of and support from informal and formal networks (Bronfenbrenner, 2001; Dunst, 2000; Trivette et al, 2010). Beyond asking which key partners are present, we must look at the quality of connections (Edwards, 2020; Edwards & Denham, 2018). This information can pinpoint strengths, potentially problematic relationships, and/or gaps we need to better address with devised or existing options across local communities.…”
Section: Discussionmentioning
confidence: 99%
“…Needs assessments may enhance family, school, and community partnerships by considering the make-up of and support from informal and formal networks (Bronfenbrenner, 2001;Dunst, 2000;Trivette et al, 2010). Beyond asking which key partners are present, we must look at the quality of connections (Edwards, 2020;Edwards & Denham, 2018). Stronger ties within one's own ethnic community can serve as a protective factor for healthy parenting practices and emotional health (Williams et al, 2017;Yakushko, 2010).…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation